Reviewers (GIST – Education and Learning Research Journal, 2022)
Gist would like to thank the following reviewers for their valuable comments and thoughtful revision: Juan Carlos Torres Rincón, Universidad de La Sabana, Colombia Jhonatan Vásquez Guarnizo, UPTC, Colombia Jair Ayala-Zárate, Educational Testing Services, Colombia Mohammad Kazemian, Islamic Azad University, Iran Enrique Vez, Universidad Veracruzana, Mexico Mauricio Arango, Universidad de Caldas, Colombia Jorge Eduardo Pineda Hoyos, Universidad de Antioquia, Colombia Victor Pavón, Universidad de Córdoba, Spain Turgay Han, Kafkas University, Turkey Juan Ríos Vega, Bradley University, USA Rigoberto Castillo, Universidad Distrital Francisco José de Caldas, Colombia Sanja Škific, University of Zadar, Croatia Alexander Ramírez, Universidad del Valle, Colombia